The impact of the purposive interpretation in refuting the suspicion of disparaging women raised against the hadith: "A people who entrust their affairs to a woman will never prosper." - Agha, Prof. Dr. Khalouk Dhaifallah Muhammad Agha Muhammad (Sulaimani Journal for Humanities, 2026)
This research aims to demonstrate the impact of purposive interpretation on understanding religious texts, especially since the apparent meaning of some of these texts may raise doubts among skeptics, as in the Prophet's saying (peace and blessings be upon him): "A people who entrust their affairs to a woman will never prosper." Therefore, this study seeks to answer the following question: What is the impact of purposive interpretation on refuting the skepticism surrounding the hadith "A people who entrust their affairs to a woman will never prosper"? To arrive at the results of this research, the researcher employed both inductive and descriptive-analytical methods. The study concluded with several key findings, the most important of which is that purposive interpretation involves attempting to uncover the intent and purpose of the Lawgiver by shifting the meaning from its apparent sense to another possible meaning supported by compelling evidence. Furthermore, the purposive interpretation of the Prophet's saying (peace and blessings be upon him): "A people who entrust their affairs to a woman will never prosper" indicates that the prohibition against women assuming public office does not diminish their dignity or status in Islam; rather, it is an act of honoring and preserving their position. Because the Sharia protected women from situations of harshness, severity, and strictness, as these do not suit their refined nature and the nature that God Almighty created them with. Islam preceded all positive laws and human civilizations in honoring women and preserving their rights. Finally, the jurists agreed that it is not permissible for a woman to assume the position of head of state (the supreme authority), citing the noble hadith under study and other valid legal evidence. They differed regarding other administrative positions that are similar in some aspects to the supreme authority, such as the ministry, the judiciary, and the like.